The transition from objectively structured practical examination (OSPE) to electronic OSPE in the era of COVID‐19. Issue 5 (11th July 2020) - Dutta, Atanu Kumar; Goswami, Kalyan; Murugaiyan, Sathishbabu; Sahoo, Sibasish; Pal, Amit; Paul, Chandramallika; Thallapaneni, Sasikala; Biswas, Soham
Abstract: The coronavirus (COVID‐19) pandemic is forcing the medical educators to innovate and embrace online education and assessment platform. One of the most significant challenges we are facing is the formative assessment of practical skills in the undergraduate medical biochemistry education. We have designed the electronic objectively structured practical examination to facilitate the formative assessment.